Osmophore diversity in the Catasetum cristatum Lindl. alliance (Orchidaceae: Catasetinae) - Franken, Evelyn P.; Pansarin, Ludmila M.; Pansarin, Emerson R. (Lankesteriana: International Journal on Orchidology, 2016)
Catasetum is a neotropical orchid genus of 130 species characterized by its unisexual flowers. They are pollinated by male Euglossini bees. It is widely know that these bees collect volatile compounds in Catasetum from structures called osmophores. However, there is little information on morpho-anatomy and histochemistry of secretory tissues for this neotropical genus and data are lacking. Based on these arguments members of the Catasetum cristatum alliance, namely C. arietinum, C. ariquemense, C. barbatum, C. carolinianum, C. cristatum, C. lanciferum, C. multifidum, C. multifissum, C. rivularium and C. semicirculatum were analyzed. The labellum of male flowers of this alliance is elongate and with fimbriate margins, possessing two protuberances and a median saccate portion. The labellum of female flowers is galeiform and there is no ornamentation. The entire adaxial surface of the labellum is secretory in both sexes, including the fimbriae of male flowers. The structure of the secretory tissue is similar among species, and they are composed of a simple epidermis and five layers of underlying parenchyma. In most species the epidermis is flat, and cells are elongated in the saccate portion. In C. ariquemense and C. carolinianum the epidermal cells are papilous, while in C. semicirculatum they have convex surface (male flowers). The histochemical analysis detected lipophilic droplets and starch grains inside the secretory cells. All characteristics observed are encountered in secretory tissues with high-energy demand, as is common in osmophores.